About the existence and uniqueness theorem for hyperbolic equation - M. E. Khalifa (International Journal of Mathematics and Mathematical Sciences)
In this paper we prove the existence and uniqueness theorem for almost everywhere solution of the hyperbolic equation using the method of successive approximations [1].